Kajian Hubungan Komponen Beban Kerja Dengan Kinerja Perawat Pelaksana Di Ruang Rawat Inap Rumah Sakit Harapan Bunda Batam - Didi Yunaspi; Zulkarnain Edward; Emil Huriani (Jurnal Keperawatan Muhammadiyah, 2020)
In the inpatient room of the Harapan Bunda Batam hospital nurses complained of excessive workloads and the number of nurses that did not match the number of patients who had to be served. High workload will reduce nurse performance. A good nursing performance will create quality implementation of a quality nursing process. The purpose of this study was to determine the relationship of workload components with the performance of implementing nurses in the inpatient room at Harapan Bunda Hospital in Batam. Descriptive analytic research design, "cross sectional" approach. Data collection was carried out from 5 to 17 January 2015 in total sampling. Data was collected by observation and using a questionnaire. Data were analyzed using Chi-Square Test. The results showed the number of patients treated was not in accordance with the number of nurses, the type of nurse nursing activities were productive, the average time for nursing nurses implementing activities was effective, the performance of implementing nurses was good for, there was a significant relationship between the number of patients, types of activities nursing with nurse nurse performance, but there is no significant relationship between the average time of nursing activities with the performance of nursing nurses in the inpatient room of the hospital. Hope Mother. Suggestions for the nursing field that the system of providing professional nursing services in inpatient installations.